Hollow Silica‐Based Porous Liquids Functionalized Mixed Matrix Membranes for CO2 Capture. Issue 20 (26th May 2021) - Liu, Shuo; Meng, Long; Fan, Jinwen
Abstract: Porous liquids (PLs) are a newly emerging type of porous materials with empty cavities and tailed functionalities, demonstrating great potential in gas capture. However, PLs used as fillers of mixed matrix membranes (MMMs) are seldom reported till now. Herein, MMMs for CO2 selective separation were prepared by incorporating hollow silica PLs into Pebax‐1657 matrix. As expected, the liquid‐like property of PLs renders excellent filler dispersion. Besides, the hollow cavities construct fast permeation diffusion channels, reducing trans‐membrane permeation resistance. More importantly, CO2 ‐philic moieties of PLs lead to superior CO2 selective permeation. Therefore, the as‐prepared MMM exhibited a CO2 permeability up to 229.5 Barrer with a CO2 /N2 selectivity up to 71.7 (241.9 % and 90.2 % increment than those of pure Pebex‐1657 membrane, respectively), surpassing the 2008 Robeson upper bound. Finally, molecular simulation was applied to verify the improved interaction between gas molecules and membrane by analyzing interaction parameters. Our work underlines the feasibility and importance of porous liquids to design advanced fillers in MMMs, which makes great promise for CO2 capture. Abstract : Porous liquids (PLs) based on hollow silica were sythesized and incorporated into Pebax polymer matrix to construct mixed matrix membranes (MMMs) for CO2 capture. As expected, the liquid‐like property of PLs renders excellent filler dispersion. Besides, the hollow cavities construct fast permeation diffusion channels, reducing trans‐membrane permeation resistance. More importantly, CO2 ‐philic moieties of PLs lead to superior CO2 selective permeation. Therefore, the as‐prepared MMM exhibited a CO2 permeability up to 229.5 Barrer with a CO2 /N2 selectivity up to 71.7.